2022
DOI: 10.1155/2022/2617752
|View full text |Cite
|
Sign up to set email alerts
|

Technological Change and Market Conditions: Evidence from Bitcoin Fork

Abstract: This article examines the impact of technological changes to cryptocurrency—known as “forking” that triggers blockchain splits—on market conditions. Despite the explicit distinction in log return distributions between the two splitting blockchains, adopting new technology does not result in a disparity in market conditions: no significant difference exists in market efficiency and long-term market equilibrium between the two splitting blockchains. Technological changes accompanying market separation do not imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
0
0
0
Order By: Relevance
“…Shanaev and Ghimire (2022) found that cryptocurrency markets are less efficient than national stock markets, with predominantly irregular seasonality periodicity that cannot be reduced to conventional weekly, monthly, or annual cycles. Kim et al (2023) and Yi et al (2023) focused on the market capitalization and information discovery speed in the Bitcoin market. It highlighted the fast information circulation in the Bitcoin market, suggesting its efficiency and robustness against the predictability of future prices based on past performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Shanaev and Ghimire (2022) found that cryptocurrency markets are less efficient than national stock markets, with predominantly irregular seasonality periodicity that cannot be reduced to conventional weekly, monthly, or annual cycles. Kim et al (2023) and Yi et al (2023) focused on the market capitalization and information discovery speed in the Bitcoin market. It highlighted the fast information circulation in the Bitcoin market, suggesting its efficiency and robustness against the predictability of future prices based on past performance.…”
Section: Literature Reviewmentioning
confidence: 99%